Long Non-Coding RNA FGD5-AS1 Induced by Chlamydia trachomatis Infection Inhibits Apoptosis via Wnt/β-Catenin Signaling Pathway - Wen, Yating; Luo, Fangzhen; Zhao, Lanhua; Su, Shengmei; Lei, Wenbo; Liu, Yi; Shi, Keliang; Li, Zhongyu (Frontiers in Cellular and Infection Microbiology, 2021)
Background Chlamydia trachomatis (Ct) is one of the most common bacterial sexually transmitted infection (STI) pathogens in the world, but the exact pathogenic mechanism still needs to be further elucidated. Long non-coding RNAs (lncRNAs) have become vital regulators in many biological processes. Their role in the interaction between Ct and host cells has not been reported. Methods Microarrays were used to study the expression profiles of lncRNAs and mRNAs in HeLa cells at 12, 24, and 40 h post-infection (hpi). Differentially expressed lncRNAs and mRNAs were verified by RT-qPCR. Coding-non-coding (CNC) network analysis showed co-expression molecules of selected lncRNA. Western blot, flow cytometry, and indirect immunofluorescence were used to detect the effect of lncRNA FGD5-AS1 on apoptosis during Ct infection. Results Compared with the uninfected group, the number of differential lncRNAs were 2,130, 1,081, and 1,101 at 12, 24, and 40 hpi, and the number of differential mRNAs was 1,998, 1,129, and 1,330, respectively. Ct induced differential expression of large amounts of lncRNAs and mRNAs in HeLa cells, indicating that lncRNAs may play roles in the pathogenesis of Ct. RT-qPCR verified six differential lncRNAs and six differential mRNAs, confirming the reliability of the microarray. Among these molecules, lncRNA FGD5-AS1 was found to be upregulated at 12 and 24 hpi. Coding-non-coding (CNC) network analysis showed that co-expressed differential molecules of FGD5-AS1 at 12 and 24 hpi were enriched in the DNA replication and Wnt signaling pathway. The downregulation of FGD5-AS1 decreased the expression of β-catenin and inhibited the translocation of β-catenin and the DNA replication, while it promoted apoptosis of the host cells. Conclusions DNA replication and apoptosis of host cells were affected by upregulating FGD5-AS1 via Wnt/β-catenin pathway during Ct infection. This study provides evidence that lncRNAs are involved in the coaction between Ct and hosts, and provides new insights into the study of lncRNAs that regulate chlamydial infection.